Analisis Penerapan Konsep Organisasi Belajar Pada AB Home Education - Farid Fachrudin; Ira Arini; Muhammad Japar (LP. Ma'arif Janggan Magetan, 2023)
Building a learning organization can be done by maximizing five models of learning organization systems that are interrelated, namely learning, organization, people, knowledge, and technology. Each of the learning organization's five components actively supports each other to get maximum results, be sustainable, and achieve organizational goals. A strong leader is a leader who always tries to learn and build a learning culture in his organization. In the current era of globalization, the concept of a learning organization is very important to adapt to the dynamic changes of the times. This study aims to analyze the extent to which AB Home Education as an educational institution has implemented the concept of learning organization and applied it in teaching and learning activities. The research method used is qualitative research by conducting interviews and researchers are directly involved as facilitators at AB Home. AB Home Education has applied the concept of learning organization, namely (1) personal mastery, (2) mental models, (3) shared vision, (4) team learning, (5) system thinking through a curriculum that is structured based on community-based education and talents management in education. The curriculum is designed with a composition of 60% activity and 40% academic.